PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT TERHADAP REAKSI INVESTOR PADA PERUSAHAAN SEKTOR PERTAMBANGAN DAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2014 – 2015 - Bagus Setia Aji; Agung Juliarto (Diponegoro Journal of Accounting, 2018)
The purpose of this research is to examine the effect of Sustainability Report disclosure on investor’s reaction on mining and manufacturer sector companies. Sustainability Report disclosure are measured by Sustainability Report Disclosure Index based on G-4 guidelines which is published by Global Reporting Initiative (GRI). The proxies used for dependent variable invertors reaction is abnormal return of share. This research is also use Return on Asset (ROA) and Return on Equity (ROE) as variable control. The population in this research are mining and manufacturer companies listed in Indonesia Stock Exchange in 2014-2015.Sampling was done by purposive sampling. Total number of used samples is 63 companies.Data analysis with descriptive analysis, the classical assumption test, and multiple regression analysis.The result of hypothesis testing shows the effect of Sustainability Report disclosure on investors reaction which is measured by abnormal return of share around the publication date of report. The information inside the sustainability report isone thing which is considered by investors to take investing decision.